VD_FINDINFO HC / 2022 / 508 vom 15. Juni 2022 - VD Tribunal cantonal (2022)
RÉCUSATION, REJET DE LA DEMANDE, DÉPENS, MAXIME DE DISPOSITION | 319 let. b ch. 1 CPC (CH), 47 al. 1 let. f CPC (CH), 49 al. 1 CPC (CH), 58 al. 1 CPC (CH)